Pengaruh Saluran Distribusi Dan Kualitas Produk Terhadap Keputusan Pembelian Pada PT Arvata Indra Jaya Parung Kabupaten Bogor - Aslam Abu Rafi; Reza Khairul Hadi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. The purpose of this study is to determine the influence of distribution channels and product quality on purchasing decisions at PT Arvata Indra Jaya Parung, Bogor Regency, both partially and simultaneously. The method used in this study is an associative quantitative method. The population at PT Arvata Indra Jaya Parung, Bogor Regency is 1,228 respondents. The sample used in this study is 92 people. The analysis in this study uses the SPSS program version 25. The data analysis method uses a simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial T test and simultaneous F test. The results of this study indicate that: There is a significant partial influence of distribution channels on purchasing decisions at PT Arvata Indra Jaya Parung, Bogor Regency. This can be proven because the distribution channel variable (X1) has a calculated T value of 7.670 > T table 1.986 with a significance level of 0.000 <0.05. There is a significant partial influence of product quality on purchasing decisions at PT Arvata Indra Jaya Parung, Bogor Regency. This is evident because the product quality variable (X2) has a calculated T-value of 9.503 > T-table 1.986, with a significance level of 0.000 < 0.05. Distribution channels and product quality simultaneously significantly influence purchasing decisions at PT Arvata Indra Jaya Parung, Bogor Regency. This is evident because the calculated F-value is 47.860 > F-table 3.100, with a significance level of 0.000 < 0.05. The coefficient of determination test results are indicated by an R-square value of 0.518, indicating that the distribution channel (X1) and product quality (X2) variables contribute 51.8% to the purchasing decision variable (Y), while the remaining 48.2% is due to other variables not examined in this study